Direct detection of stringent alarmones (pp)pGpp using malachite green - Schicketanz, Muriel; Petrová, Magdalena; Rejman, Dominik; Sosio, Margherita; Donadio, Stefano; Zhang, Yong Everett (Microbial cell (Graz, Austria), 2024)
The alarmone (p)ppGpp serves as the signalling molecule for the bacterial universal stringent response and plays a crucial role in bacterial virulence, persistence, and stress adaptation. Consequently, there is a significant focus on developing new drugs that target and modulate the levels of (p)ppGpp as a potential strategy for controlling bacterial infections. However, despite the availability of various methods for detecting (p)ppGpp, a simple and straightforward detection method is needed. In this study, we demonstrated that malachite green, a well-established compound used for phosphate detection, can directly detect (p)ppGpp and its analogues esp., pGpp. By utilizing malachite green, we identified three new inhibitors of the hydrolase activity of SpoT, one of the two RelA-SpoT homolog (RSH) proteins responsible for making and hydrolyzing (p)ppGpp in Escherichia coli. These findings highlight the convenience and practicality of malachite green, which can be widely employed in high-throughput studies to investigate (pp)pGpp in vitro and discover novel regulators of RSH proteins.
Keywords: thermorubin; pGpp; pppGpp; ppGpp; malachite green; SpoT